Prevalence and Characteristics of Smoking Behavior Among Health and Recreation Students at Universitas Negeri Padang - Reza Ardhana; Nuridin Widya Pranoto; Fahmil Haris; Nugroho Susanto (STKIP Pasundan, 2026)
This study described the prevalence and characteristics of smoking behavior among students of the Department of Health and Recreation at Universitas Negeri Padang. A quantitative descriptive survey involved 100 active students selected purposively. Data were collected using a structured questionnaire, observation, and documentation and analyzed with frequencies, percentages, mean scores, respondent achievement levels, item-total correlations, and Cronbach's alpha. Forty-four percent of respondents smoked. Among the 44 smokers, daily smoking predominated; most consumed 5-10 cigarettes per day, initiated before age 18, and smoked mainly while gathering with friends. All smokers had friends who smoked, and most had smoking parents. The 13-item scale showed satisfactory item validity and high internal consistency (Cronbach's alpha = .92). Smoking was strongly embedded in peer and family environments. Integrated cessation support, peer-norm interventions, stress-management alternatives, and consistent smoke-free campus enforcement are recommended.